Insulin resistance reduction after sustained virological response with direct acting antiviral: Not every population improves - de Andrade, Vanessa Gutierrez [UNESP]; Yamashiro, Fábio da Silva [UNESP]; Oliveira, Cássio Vieira [UNESP]; Moreira, Alecsandro [UNESP]; Winckler, Fernanda Cristina [UNESP]; Silva, Giovanni Faria [UNESP] (FapUNIFESP (SciELO), 2018)
Background – Hepatitis C virus (HCV) infection is a serious public health problem, that affects approximately 170 million people worldwide. Chronic HCV infection is associated with hepatic insulin resistance and an increased risk of diabetes HCV-infected patients has been well documented. Objective – To assess the homeostasis model assessment of insulin resistance (HOMA-IR) index in patients treated with direct acting antiviral (DAAs) medication in the sustained virological response (SVR), categorized by the presence or absence of cirrhosis. Methods – A prospective study was conducted. Data were collected at the beginning of treatment (t-base) and in the twelfth week after the completion of treatment (t-SVR12). The inclusion criteria were presence of: HCV infection (RNA-HCV positive), age ≥18 years, completion of DAAs’ therapy, and presence of diabetes with use of oral hypoglycemic agents. All samples were collected during the study period. The exclusion criteria were: presence of HBV/HIV co-infection, hepatocellular carcinoma at baseline, diabetic patients taking insulin and transplanted patients (liver/kidney). Fibrosis was assessed by hepatic elastog-raphy or biopsy (METAVIR). Cirrhosis was determined by clinical results or imaging. HOMA-IR was calculated as fasting insulin (μU/mL) × fasting glucose (mmol/L)/22.5) The patients were divided into two groups: the general study population (all patients, including the diabetic patients) and the special population (patients with normal values of HOMA-IR, which is >2.5, and without diabetes). The delta HOMA-IR value was calculated as: HOMA-IR at t-base – HOMA-IR at t-SVR12. For the descriptive statistical analysis, the paired t-test and generalized linear model assuming the log binding function were performed. A P value of < 0.05 was considered significant. Results – We included 150 patients, and 75 were cirrhotic. The mean age was 55.3±9.97 and body mass index was 27.4±5.18. Twenty-two (14.67%) were diabetic patients using oral hypoglycemic agents, and 17 (11%) were cirrhotic. In the general study population, the mean glucose and HOMA-IR values increased at t-SVR12, but insulin decreased. Delta HOMA-IR was negative at t-SVR12, but there was no significant difference. Excluding diabetic patients and those with normal HOMA-IR values (<2.5), mean glucose, insulin and HOMA-IR decreased at t-SVR12. Delta HOMA-IR decreased significantly at t-SVR12 (P: 0.02). Conclusion – In the general population, glucose and HOMA-IR values increased at t-SVR12, but insulin decreased. In the special population, glucose, insulin, HOMA-IR and Delta HOMA-IR decreased at t-SVR12.
Redução da resistência à insulina após resposta virológica sustentada com agentes antivirais diretos: Nem toda população melhora
Keywords: Antiviral agents; Hepatitis C; Insulin resistance